Better economy in field running than on the treadmill: evidence from high-level distance runners - Mooses, M; Tippi, B; Mooses, K; Durussel, J; Mäestu, J (Biology of Sport, 2015)
Given the ongoing interest in ways to improve the specificity of testing elite athletes in their natural environment, portable metabolic systems provide an opportunity to assess metabolic demand of exercise in sport-specific settings. Running economy (RE) and maximal oxygen uptake ( ·VO 2 max) were compared between track and treadmill (1% inclination) conditions in competitive level European distance runners who were fully habituated to treadmill running (n = 13). All runners performed an exercise test on running track and on treadmill. While ·VO 2 max was similar on the track and on the treadmill (68.5 ± 5.3 vs. 71.4 ± 6.4 ml∙kg -1 ∙min -1 , p = 0.105, respectively), superior RE was found on the track compared to the treadmill (215.4 ± 12.4 vs. 236.8 ± 18.0 O2 ml∙kg -1 ∙km -1 , p < 0.001). RE on the track was strongly correlated with RE on the treadmill (r = 0.719, p = 0.006). The present findings indicate that high-level distance runners have significantly better RE but not ·VO2max on the track compared to treadmill. This difference may be due to biomechanical adjustments. As RE is strongly correlated between the two conditions, it would be reasonable to assume that interventions affecting RE on the treadmill will also affect RE on the track.